Rural Health Services Disruption: An Evaluation of Nursing's Professional "Positionality" - Smith, Jessica G. (Nursing philosophy, 2026)
Rural health services disruption poses a significant global challenge, with nurses at the forefront of its impact. From supply chain disruptions and workforce shortages to climate events and demographic shifts, these challenges consistently threaten the provision of healthcare in rural areas. In the United States, rural hospital closures exemplify the disruption of rural health services. Socio-political impasses disrupt efforts to curb rural hospital closures and appear to be rooted in networks of political ideologies and economic imperatives for profit. Nurses working in rural communities that experience a rural hospital closure are burdened with navigating disruptions and systemic barriers while simultaneously striving to fulfil their professional obligations to care for others. A bedrock for a consistent professional stance, or position statement that supports preparation for and contemporary nursing practice in rural communities, requires philosophical groundwork to define the profession's positionality in relation to rural nursing and rural nursing practice. By positioning health as a fundamental human right for rural residents, nursing as a profession holds the potential to lead systemic change for greater rural healthcare access. Grounded in the ICN Code of Ethics for Nurses, nurses globally could fulfil their social contract through advocacy for equitable access to services for rural populations. It is essential for nurses to actively engage as a professional group with rural communities to influence systemic reforms. Defining a professional nursing positionality could spark a collective move from being a casualty of disruption to igniting agency in professional responses that move beyond individualistic socio-political and economic divisions to a professional position of advocating for equity in rural healthcare delivery.